English Language Exposure, Communicative Engagement, and Mentorship Influence on Internship Preparedness Among Pre-Service English Teachers - Dimzon, Salita D. (Journal of Qualitative Research in Education, 2025)
This explanatory sequential mixed-methods study investigated how English language exposure, communicative engagement, and mentorship influence shape internship preparedness among 69 pre-service English teachers from a state university in Iloilo City, Philippines. The quantitative phase measured students’ levels of exposure, engagement, mentorship experience, and perceived readiness for teaching using validated Likert-type instruments, while the qualitative phase explored contextual factors that clarified emerging statistical patterns. Findings indicated that the participants demonstrated moderate English language exposure, largely derived from digital and entertainment media, whereas interpersonal and home-based communicative use remained limited. Despite this moderate exposure, students reported high levels of internship preparedness, although significant differences were observed between sections, signaling uneven developmental opportunities. Correlation analysis revealed no significant relationship between exposure and preparedness, indicating that passive or input-dominant exposure does not directly foster teaching confidence or pedagogical readiness. Qualitative insights emphasized the critical role of communicative engagement and mentorship particularly consistent modeling, structured feedback, and guided pedagogical practice in shaping students’ readiness for classroom realities. Overall, the study underscores that internship preparedness is a multifaceted construct influenced more by quality engagement and mentorship depth than by the frequency of language exposure. Implications highlight the need for teacher education programs to enhance communicative practice, structured learning experiences, and supervisory systems that strengthen the transition from coursework to professional teaching.